2021
DOI: 10.1002/jhbp.947
|View full text |Cite
|
Sign up to set email alerts
|

Nitazoxanide versus rifaximin in preventing the recurrence of hepatic encephalopathy: A randomized double‐blind controlled trial

Abstract: Background/Purpose: Hepatic encephalopathy (HE) is a neuropsychiatric complication of liver cirrhosis. HE is associated with poor survival and detrimental effects on quality of life (QOL). The drawbacks of the long-term use of rifaximin in HE necessitates searching for alternative therapies. In this context, our study aimed at evaluating the safety and efficacy of nitazoxanide (NTZ) as compared to rifaximin (RFX) in preventing the recurrence of HE and assessing its impact on QOL. Patients and Methods: This pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…In experimental studies in mice, nitazoxanide (100 mg/kg/d) attenuated dyslipidaemia, liver steatosis [ 204 ], fibrosis, inflammation, and HCB, demonstrating synergistic effects with the pan-PPAR agonist elafibranor [ 205 ]. Moreover, the anti-anaerobic activity of nitazoxanide may determine its use in preventing the recurrence of hepatic encephalopathy as a viable alternative to rifaximin (NCT04161053) [ 206 ].…”
Section: Other Agentsmentioning
confidence: 99%
“…In experimental studies in mice, nitazoxanide (100 mg/kg/d) attenuated dyslipidaemia, liver steatosis [ 204 ], fibrosis, inflammation, and HCB, demonstrating synergistic effects with the pan-PPAR agonist elafibranor [ 205 ]. Moreover, the anti-anaerobic activity of nitazoxanide may determine its use in preventing the recurrence of hepatic encephalopathy as a viable alternative to rifaximin (NCT04161053) [ 206 ].…”
Section: Other Agentsmentioning
confidence: 99%
“…Nitazoxanide (NTZ) is an antimicrobial agent with wide safety profile that has broad-spectrum activity against urease-producing bacteria leading to decreased ammonia production. 52,53 This antibiotic has been evaluated in HE treatment as an alternative to rifaximin. 52 In a pilot study including 34 patients with grade 2-3 HE, administration of NTZ for 1 week showed similar efficacy to rifaximin, and it was superior in quality of life improvement.…”
Section: Nonabsorbable Antibioticsmentioning
confidence: 99%
“…52,53 This antibiotic has been evaluated in HE treatment as an alternative to rifaximin. 52 In a pilot study including 34 patients with grade 2-3 HE, administration of NTZ for 1 week showed similar efficacy to rifaximin, and it was superior in quality of life improvement. 54 A randomized trial of 120 patients with cirrhosis and overt HE showed that NTZ plus lactulose administration vs lactulose and placebo resulted in a significantly better improvement in Clinical HE Staging Scale score (P < .001).…”
Section: Nonabsorbable Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…A newer agent currently used in clinical trials for the treatment of HE is nitazoxanide, a broad-spectrum antibiotic and antiparasitic agent with activity against gut anaerobes. However, studies on the effect of microbiota composition are still lacking (Glal et al, 2021).…”
Section: Antibioticsmentioning
confidence: 99%